PRODUCTION FUNCTIONS AND ECONOMIC EFFICIENCY - Shakarov Allayor Baratovich; Avazova Charos Murod qizi (Web of Journals Publishing, 2024)
This article explores the role of production functions in analyzing economic efficiency. Production functions, which describe the relationship between input factors (such as labor, capital, and technology) and output, are crucial for understanding how resources are allocated in the production process. The study focuses on various types of production functions, including the Cobb-Douglas and Constant Elasticity of Substitution (CES) models, and examines their applications in assessing the efficiency of firms and industries. By analyzing these models, our article sheds light on how economies can maximize outputs while minimizing inputs, providing insights into productivity improvements and optimal resource utilization. The implications for policy and business strategies are also discussed, offering guidance for enhancing economic efficiency across different sectors.
Keywords: Production functions, economic efficiency, cobb-douglas model, constant elasticity of substitution, input-output analysis, resource allocation, productivity, firm efficiency, optimal resource utilization.